Arbitration of Legacy VGA Interface for Multiple Video Cards - Vignatti, Tiago; Zanoni, Paulo R.; Oliveira, Ander C. de; Bona, Luis C. E. de; Silva, Fabiano (Anais do Workshop de Sistemas Operacionais (WSO); 2008: Anais do V Workshop de Sistemas Operacionais, 2008)
When multiple applications use the legacy Video Graphics Array (VGA) interface to communicate with different graphics devices attached to the same machine, problems inherited by the old Industry Standard Architecture (ISA) system happen. If the accesses to these graphics devices are not correctly controlled, an access made using that interface might be decoded by the wrong graphics card. Since the Peripheral Component Interconnect (PCI) and the Accelerated Graphics Port (AGP) standards are compatible with ISA, this problem remains in most modern devices. This paper presents a solution independent of the application to this problem. It consists of a conceptual architecture, which defines an arbiter that manages all the VGA accesses and an user space interface used by the applications. An implementation using the Linux Kernel and the X server is also presented. The results of the experiments show that there is no significant performance loss.